Effect of water distribution in gas diffusion layer on proton exchange membrane fuel cell performance. (11th January 2021) - Yue, Like; Wang, Shixue; Araki, Takuto; Utaka, Yoshio; Wang, Yulin
Abstract: Water management of proton exchange membrane fuel cells remains a prominent issue in research concerning fuel cells. In this study, the gas diffusion layer (GDL) of a fuel cell is partially treated with a hydrophobic agent, and the effect of GDL hydrophobicity on the water distribution in the fuel cell is examined. First, the effect of the position of the cathode GDL hydrophobic area relative to the channel on the fuel cell performance is investigated. Then, the water distribution in the fuel cell cathode GDL is observed using X-ray imaging. The experimental results indicate that when the hybrid GDL's hydrophobic area lies on the channel, water tends to accumulate under the rib, and the water content in the channel is low; this improves the fuel cell performance. When the hydrophobic area is under the rib, the water distribution is more uniform, but the performance deteriorates. Highlights: Performance enhancement of proton exchange membrane fuel cells was examined. Gas diffusion layer was partially treated with a hydrophobic agent. Effect of gas diffusion layer hydrophobicity on water distribution was studied. Water distribution in fuel cell cathode gas diffusion layer studied by X-ray imaging.